Współdziałanie organów administracji rządowej i samorządowej w stanach nadzwyczajnych - Korczak, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
he system of territorial self-government is based on independence of its tiers — communes, districts and voivodships — which is expressed in their independence in two relational systems: between tiers within the system of territorial self-government, and between tiers of local self-government and governmental authorities. However, at the same time, independence does not exclude their cooperation in both relational systems because agreements, unions, and associations, in which tiers of territorial self-government participate, and also associations of tiers of territorial self-government with governmental authorities, allow for common performance of public tasks or for their delegation. The above-mentioned forms are not initiated without the will of tiers of local self-government and they do not build hierarchical dependency between their participants. The imposition of every extraordinary measure has a great influence on those relations because, despite the declaration of normal functioning of public authorities in case of the imposition of extraordinary measure, not only extraordinary competences of heads of the communes and starost’s in relation to entities functioning on the territory of their jurisdiction arise but also atypical relations between starost, commune head, and governor, and even between central authorities and starost. The aim of this article is to identify and analyze the mentioned relations which are provided by provisions of acts regulating conditions of imposition of every extraordinary measure.
Keywords: administracja rządowa; administracja samorządowa; współdziałanie; stany nadzwyczajne